PENGARUH TERPAAN TAYANGAN “SUARA HATI ISTRI” DI INDOSIAR TERHADAP KECEMASAN PERNIKAHAN PEREMPUAN PRA NIKAH DI DESA SRIKANDANG - Feni Ersa Silviana; Sri Wahyuningsih (Jurnal Komunikasi dan Budaya, 2021)
Television is one of the mass media that is widely used by Indonesian people as a medium of information, education, and even entertainment. But not infrequently this television show affects the perception and attitude of the audience. The purpose of this study was to determine whether there was an effect of exposure to the FTV show "Suara Hati Istri" in Indosiar on the marriage anxiety of pre-wedding women in Srikandang village, Bangsri district, Jepara district and to find out how much influence exposure to the FTV show "Suara Hati Istri" in Indosiar had on marriage anxiety of pre-wedding women in Srikandang village, Bangsri district, Jepara district. This study uses a quantitative approach with a survey method, the data collection technique carried out by the researcher is using a questionnaire distributed online to 219 respondents. To be able to know the results of the research that has been done, the data obtained were analyzed by several analytical techniques, which include reliability testing, validity testing, bivariate correlation analysis, simple linear regression analysis, and coefficient of determination test. The results of this study indicate that there is a significant influence between the variable exposure to the FTV show "Suara Hati Istri" in Indosiar on the marriage anxiety variable of pre-wedding women in Srikandang village, which is 60.4%. So that there are 39.6% of this anxiety is influenced by other factors outside the research that has been done.